Johannes V. Jensens programskrift »Den gotiske Renais- sance« – nogle tekstkritiske bemærkninger - Jørgensen, Aage (Danske Studier, 2024)
Johannes V. Jensen made his entrance onto the literary scene with novels (Danskere, 1896; Einar Elkær, 1898) rooted in the fin de siècle atmosphere of the time. Even Kongens Fald (1900–01) may be considered a novel of decadence. In Den gotiske Renaissance (1901), however, he turned his attention to »Kendsgerningerne«, i.e. the reality of the modern world and its technological marvels. The book included critical observations from the 1898 Spanish-American war (as experienced in Madrid) and enthusiastic reports from the 1900 World Fair in Paris. The Paris portion of Den gotiske Renaissance was based on sixteen articles published in the newspaper Social-Demokraten. One of them has been »forgotten«, first by the author himself when he edited the book, then by his bibliographers, and finally, for that very reason, by subsequent scholarship. The editorial process involved in reshaping the articles into a section of a book is described in some detail with regard to insertions and omissions and to the entire rearrangement of the textual material in order to set Jensen’s programme in the sharpest possible relief.